Treaties, trenches, mud, and blood ebook A world war i tale. - Hale, Nathan (Nathan Hale's Hazardous Tales, 2014)
New York Times Bestselling Series! âThese books are, quite simply, brilliant. . . . Thrilling, bloody, action-packed stories from American history.â â New York Times Â  Learn about the most well-known battles (and little-known secrets) of World War I with the New York Times bestselling graphic novel series! Â  In 1914, the worldâs biggest countries (and some of its smallest, too) were gearing up for a massive fight. Land, history, geographyâeach country went to war for different reasons and with different resources. But most ended up the same: sending their young men to fight for their lives in the mud, on the sea, and in the air, in a conflict that would eventually claim more than 9 million lives.Â Â Â Â Â Â Â Â Â Â  Â  World War I, âThe Great War,â or âThe War to End All Warsâ was fought along thousands of miles of front-line trenches, with mechanized weapons, and dangerous new weapons like machine guns and mustard gas. It left behind a world that was scarred, angry, and traumatized. Its horrifying lessons are still being studied today. Â  Nathan Haleâs Hazardous Tales! Read them allâif you dare! One Dead Spy: A Revolutionary War Tale (Nathan Haleâs Hazardous Tales #1) Big Bad Ironclad!: A Civil War Tale (Nathan Haleâs Hazardous Tales #2) Donner Dinner Party: A Pioneer Tale (Nathan Haleâs Hazardous Tales Book #3) Treaties, Trenches, Mud, and Blood: A World War I Tale (Nathan Haleâs Hazardous Tales #4) The Underground Abductor: An Abolitionist Tale about Harriet Tubman (Nathan Haleâs Hazardous Tales #5) Alamo All-Stars: A Texas Tale (Nathan Haleâs Hazardous Tales #6) Raid of No Return: A World War II Tale of the Doolittle Raid (Nathan Haleâs Hazardous Tales #7): Lafayette!: A Revolutionary War Tale (Nathan Haleâs Hazardous Tales #8) Major Impossible: A Grand Canyon Tale (Nathan Haleâs Hazardous Tales #9) Blades of Freedom: A Tale of Haiti, Napoleon, and the Louisiana Purchase (Nathan Haleâs Hazardous Tales #10) Cold War Correspondent: A Korean War Tale (Nathan Haleâs Hazardous Tales #11)